2016
DOI: 10.4314/jasem.v20i3.29
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and bacteriological characteristics of rainwater harvested from rooftops in Esan-West Local Government Area of Edo State, Nigeria

Abstract: Due to scarcity of potable water, rainwater harvesting from rooftop has been favoured as an alternative source of water supply by most rural communities in Nigeria. This study investigated the physicochemical and bacteriological characteristics of rainwater harvested from three different rooftop sheets in Esan West Local Government Area, Edo State. Parameters investigated include pH, TSS, TDS, Turbidity, Acidity, Ca2+, Fe, Pb, Cr, TBC, TCC and E-coli. The results showed that mean values of harvested rainwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Ibikunle, Ajayi [40] explored the activity concentrations of some natural radionuclides in rainwater samples collected from different rooftops and sources in Akure, Ondo state. Rainwater captured from rooftops in Esan-West Local Government Area of Edo State, Nigeria, was studied for its physicochemical and bacteriological properties [41].…”
Section: *Correspondingmentioning
confidence: 99%
“…Ibikunle, Ajayi [40] explored the activity concentrations of some natural radionuclides in rainwater samples collected from different rooftops and sources in Akure, Ondo state. Rainwater captured from rooftops in Esan-West Local Government Area of Edo State, Nigeria, was studied for its physicochemical and bacteriological properties [41].…”
Section: *Correspondingmentioning
confidence: 99%
“…Ca 2+ in rain water mainly originates from daytime convection and vehicle/wind-driven roadside dust (Zhao et al 2013). In Nigeria also, rain water samples showed high Ca concentrations (69.5mg/L-122.3mg/L) for on set of rain and between 40.1mg/L-115.7mg/L for peak of rain (Ezemonye et al 2016).Other ions, like Na + , K + , Cland Mg 2+ arise from natural sources. Chughtai et al (2014) also reported sources of Ca 2+ , Mg 2+ and K + ions in rain water as dust from land surfaces and oceanic salts in the atmosphere.…”
Section: Fig 1 Map Of Selected Areas For Samplingmentioning
confidence: 99%